2014
DOI: 10.5539/gjhs.v6n5p46
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Women's Personal Experiences of Giving Birth in Gonabad City: A Qualitative Study

Abstract: Background:Women’s health is an important task in society. The aim of this qualitative study that used a phenomenological approach was to explain women’s personal experiences of giving birth in Gonabad city that had positive experiences of giving birth in order to establish quality cares and the related factors of midwifery cares for this physiological phenomenon.Methods:The participants were 21 primiparae women who gave a normal and or uncomplicated giving birth in the hospital of Gonabad University of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Providing a specific environment for every woman in labour to enjoy a quiet place without noise and with mild colours and respecting the privacy of patients can have a considerable role in the satisfaction of mothers and desirable experience of childbirth (Oyira et al., 2016). Providing a secure and appropriate environment for childbirth, support of women by midwifery personnel, giving the real explanation of childbirth process in a simple language and avoiding unnecessary interventions that are provided to all women regardless of their needs can be effective in creating a positive experience of childbirth (Askari, Atarodi, Torabi, & Moshki, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Providing a specific environment for every woman in labour to enjoy a quiet place without noise and with mild colours and respecting the privacy of patients can have a considerable role in the satisfaction of mothers and desirable experience of childbirth (Oyira et al., 2016). Providing a secure and appropriate environment for childbirth, support of women by midwifery personnel, giving the real explanation of childbirth process in a simple language and avoiding unnecessary interventions that are provided to all women regardless of their needs can be effective in creating a positive experience of childbirth (Askari, Atarodi, Torabi, & Moshki, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In all of the included studies, researchers aimed to explore or provide a description of women's experiences, needs, or perceptions of their intrapartum care provided by midwives (see Supplemental Table S1). The studies were conducted in Europe (Fraser, 1999;Karlstrom et al, 2015;Lavender et al, 1999;McNeils, 2013), the Middle East (Aktas & Aydin, 2019;Askari et al, 2014;Deliktas Demirci et al, 2019;Iravani et al, 2015), Asia (Anwar et al, 2014;Khresheh et al, 2019;Kuo et al, 2010), and Africa (Afaya et al, 2017;Chadwick et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Research aims and methods were appropriate in most studies. Recruitment strategies were unclear in four studies (Askari et al, 2014;Karlstrom et al, 2015;Lavender et al, 1999;McNeils, 2013), whereas researchers clearly reported data collection methods for most studies. Not all researchers clarified whether they critically examined their own roles, potential biases, and influences in formulating research questions and collecting data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the quality of prenatal care is a criterion sine qua non, because it will provide the basis for the woman to decide on her body, agree or disagree with the procedures recommended during the delivery and childbirth care, and even, on the way of delivery. 42 Moreover, adequate prenatal care has the potential to destabilize inappropriate discourse on safe, convenient, and aseptic cesarean culture and the cultural discourse of normal birth that involves risks is painful and time-consuming, 33 that the dissemination of scientific knowledge and strategies, programs and public policies of health directed towards the puerperal pregnancy cycle are shown to be antagonistic.…”
Section: /16mentioning
confidence: 99%